Identification of the gene associated with the recurring chromosomal translocations t(3;14)(q27;q32) and t(3;22)(q27;q11) in B-cell lymphomas. - Baron, B W (1993)
Chromosomal translocations involving chromosome 3, band q27, are among the most common rearrangements in B-cell non-Hodgkin lymphoma. From a bacteriophage lambda library prepared from a lymphoma characterized by a t(3;14)(q27;q32), genomic clones were isolated using a probe from the immunoglobulin heavy chain locus (IGH) joining region. In addition to clones containing an apparently normal IGH rearrangement, others were found to contain one of the translocation breakpoint junctions. Normal chromosome 3 sequences and the reciprocal breakpoint junction were subsequently isolated. DNA probes on each side of the chromosome 3 breakpoint hybridized at high stringency to the DNA of various mammalian species, demonstrating evolutionary conservation. One such probe from the presumptive der(3) chromosome detected an 11-kilobase transcript when hybridized to RNA of B- and T-cell lines. A probe made from partial cDNA clones isolated from a T-cell line hybridized with genomic DNA from both sides of the chromosome 3 breakpoint, indicating that the t(3;14) is associated with a break within the gene on chromosome 3. In situ chromosomal hybridization revealed that the same gene is involved in the t(3;22)(q27;q11). Preliminary nucleotide sequencing shows no identity of the cDNA to gene sequences in available data banks. We propose the name BCL6 (B-cell lymphoma 6) for this gene, since it is likely to play a role in the pathogenesis of certain B-cell lymphomas.